On the standardization of fuel and electricity consumption for hybrid vehicles (Международный научный журнал «Инженер», 2026)
The article addresses the issues of standardizing fuel and electricity consumption for hybrid vehicles in the context of the transition to energy-efficient and environmentally oriented transport. The relevance of developing unified methodological approaches to establishing standards for the consumption of fuel and energy resources is substantiated, taking into account the requirements of the current legislation of the Republic of Uzbekistan in the field of energy saving and energy efficiency improvement. The operational features of hybrid vehicles combining an internal combustion engine and an electric drive are analyzed, as well as the influence of driving modes, battery state of charge, and energy recuperation processes on actual fuel and electricity consumption.A methodology for conducting full-scale operational tests under real operating conditions is presented, including requirements for the technical condition of the tested vehicles, the procedure for control measurements, and an algorithm for statistical processing of measurement results. Calculation formulas for determining actual and average fuel consumption, estimating measurement errors, and forming confidence intervals are provided. An approach to calculating the standardized electricity consumption for charging traction batteries is considered, taking into account their nominal capacity, charging equipment efficiency, and operating factors.